Development of a performance-related framework for production quality control with ideal cracking and rutting tests. (20th November 2020) - Zhou, Fujie; Hu, Sheng; Newcomb, Dave
Highlights: The ideal cracking test (IDEAL-CT) and the ideal rutting test (IDEAL-RT) are simple, practical and performance-related tests, and both of the tests are good candidates for production quality control (QC) tests. It is feasible and practical to use the 30 min. fan/30 min. water bath for conditioning the IDEAL-CT and -RT specimens immediately extruded from the SGC mold. A performance-related production QC framework is recommended, including three major aspects of asphalt mixes: laboratory compaction density/rice specific gravity, cracking and rutting resistances. Abstract: Many state departments of transportation (DOTs) are in the process of developing or implementing performance specifications for asphalt mixes. In addition to balanced mix design (BMD) methods, another critical component of a performance specification is production quality control (QC). Current production QC testing, including asphalt binder content, aggregate gradation, and laboratory compaction density, does not directly relate to mix performance. To ensure what is produced at the plant is similar to what was originally designed in the laboratory, performance tests should be part of the production QC testing. This paper first identifies two simple, practical, performance related tests suited for production QC: Ideal cracking test (IDEAL-CT) and Ideal shear rutting test (IDEAL-RT). Next, the correlations between the IDEAL-CT and -RT with cracking and rutting tests commonly used by DOTs are presented to examine whether these two simple tests still can be used for production QC even if cracking or rutting tests other than the IDEAL-CT and -RT are used for BMD. Furthermore, this paper addresses a practical question: how to rapidly cooling compacted specimens to a testing temperature for QC. This paper also discusses how to establish acceptable QC criteria for the IDEAL-CT and -RT during mixture design. Based on the information presented, this paper recommends a performance-related production QC framework: IDEAL-CT for cracking resistance, IDEAL-RT for rutting resistance, and laboratory compaction density. As demonstrated in a contractor's QC lab, it is feasible to conduct the new production QC testing on a sublot (say 500 tons of mix production) basis.